The emergence of market monitoring in Japanese banks: Evidence from the subordinated debt market - Imai, Masami (Journal of Banking & Finance, 2007)
This paper uses a unique data set on the spreads of subordinated debts issued by Japanese banks to investigate the presence of market monitoring. The results show that subordinated debt investors punished weak banks by requiring higher interest rates. Moreover, I find that the spreads and the sensitivity of spreads to Moody’s bank ratings both increased dramatically after the Japanese government allowed a large city bank, Hokkaido Takushoku Bank, to fail and passed the Financial Reform Act and the Rapid Revitalization Act in the late 1990s. These results suggest that the decline of conjectural guarantee led to the emergence of market monitoring. In addition, I find the relationship between spreads and accounting measures of bank risk to be quite fragile.